Entrenchment Hypothesis and Insider Institutional Ownership: Empirical Evidence from Indonesia Capital Market - Hermeindito Hermeindito (UNIVERSITAS KALBIS, 2023)
The aim of this study is to examine the effect of insider institutional ownership on firm value. Indonesian firms have unique characteristic ownership structures which are dominated by insider institutional ownerships rather than managerial ownerships. This study develops model of entrenchment hypothesis that explain the behavior of insider institutional ownership and value of firm. Data for this study are financial ratios and stock price with period of 1994-2008 from non-financial firms that listed on Indonesia Stock Exchange. Using three-stage least squares in the equation system, this study found there is M-shaped relationship between insider institutional ownership and firm value. The research finding is parallel with Hermalin and Weisbach (1991) that found M-shaped relationship between managerial ownership and firm value.